High-hardness precise injection mold and preparation process thereof

By using laser cladding technology to form a cladding layer with low thermal conductivity on the surface of precision injection molds, and adding components such as epoxy silicone resin to the coating, the hysteresis effects and defects that occur during the injection molding process are solved, and a protective layer with high hardness, wear resistance and superhydrophobicity is achieved, extending the service life of the mold and improving product quality.

CN119589896APending Publication Date: 2025-03-11GUANGZHOU JINGHONG TECH CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411824943.6
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-12
Publication Date
2025-03-11

AI Technical Summary

Technical Problem

Existing precision injection molds are prone to defects caused by hysteresis effects, reduced flow filling capacity, warping, shrinkage and cooling during the injection molding process, and the use of fluorine-containing compounds is not conducive to the environment and human health.

Method used

Laser cladding technology is used to form a cladding layer with low thermal conductivity on the surface of the mold, Ni15 and composite zirconia are used as the cladding composite material, and components such as epoxy silicone resin and aminolated molybdenum disulfide are added to the coating to form a protective layer with high hardness, wear resistance, high temperature resistance and superhydrophobicity.

Benefits of technology

It improves the precision and service life of the mold, improves the apparent quality and mechanical properties of injection molded products, and avoids the use of harmful fluorine-containing compounds.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure SMS_1
    Figure SMS_1
Patent Text Reader

Abstract

The invention relates to the technical field of injection molds, in particular to a high-hardness precise injection mold and a preparation process thereof.A laser cladding method is adopted, a cladding layer with low heat conductivity is prepared on the inner surface of the mold, and Ni15 and composite zirconium oxide are mixed to serve as a cladding composite material; ni15 is used as powder, and pre-cladding is carried out on the surface of mold matrix steel; the composite zirconium oxide is prepared by the following steps: preparing yttrium-cerium co-doped zirconium oxide by adopting a combustion synthesis method in which citric acid is used as a fuel and ethylene glycol is used as an additive, carrying out modification treatment on the yttrium-cerium co-doped zirconium oxide, and growing an organic framework on the yttrium-cerium co-doped zirconium oxide by adopting a hydrothermal method; epoxy organic silicon resin, composite zirconium oxide and aminated molybdenum disulfide are used as fluoride-free protective paint.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of injection molds, in particular to a high-hardness precision injection mold and a preparation process thereof. Background Art

[0002] With the development of society, injection molding has been widely used in the fields of precision instruments, information communication, aerospace, etc. Precision injection molding refers to the method of producing high-precision and high-surface quality plastic products.

[0003] The cavity surface of the mold used for precision injection molding has a precise structure, which makes it easy for the melt to cause problems such as aggravated hysteresis effect and reduced flow filling capacity during filling. The yield rate of the product is subject to defects caused by warping, shrinkage, cooling, etc. during the molding process. At the same time, in order to easily separate the finished product from the mold, fluorine-containing compounds are usually used as mold coatings. However, the large-scale use of fluorine-containing compounds is not conducive to environmental protection and human health. Summary of the invention

[0004] The purpose of the present invention is to provide a high-hardness precision injection mold and a preparation process thereof to solve the problems in the prior art.

[0005] In order to solve the above technical problems, the present invention provides the following technical solutions: A method for preparing a high-hardness precision injection mold comprises the following steps: S1: grinding, washing and drying the mold in sequence to obtain a clean mold; S2: Using Ni15 as powder, laser cladding treatment is first performed on the surface of a clean mold to form a cladding base layer to obtain a pre-treated mold; S3: Ni15 and composite zirconia are mixed as a cladding composite material, and laser cladding treatment is performed on the surface of the pretreated mold to form a cladding layer to obtain a cladding mold; S4: Mixing composite zirconium oxide, amino molybdenum disulfide, epoxy silicone resin and solvent to obtain a protective coating; S5: spraying the protective coating on the surface of the mold after cladding, curing, forming a protective layer, and obtaining a high-hardness precision injection mold.

[0006] Furthermore, the working conditions of the laser cladding treatment are: spot diameter 3 mm, power 1.8 KW, scanning speed 700 mm / min, and multi-pass overlap rate 40%.

[0007] Furthermore, in the cladding composite material, the mass ratio of Ni15 to composite zirconia is 2:1.

[0008] Furthermore, the working conditions of the spraying treatment are: spraying pressure 0.5-0.7 MPa, spraying rate 7-9 m / min.

[0009] Furthermore, the protective coating comprises, by weight, 1-3 parts of composite zirconium oxide, 1-2 parts of amino molybdenum disulfide, 12-30 parts of epoxy silicone resin, and 52-83 parts of solvent.

[0010] Furthermore, the mass ratio of the sum of the mass of the composite zirconium oxide and the amino molybdenum disulfide to the epoxy silicone resin is 1:6.

[0011] Further, the preparation of amination molybdenum disulfide comprises the following steps: Molybdenum disulfide powder and n-butyl lithium hexane solution are mixed, transferred to an autoclave, kept warm at 88-92°C for 3-4 hours, filtered, washed, and dried to obtain pretreated molybdenum disulfide; the pretreated molybdenum disulfide and deionized water are mixed, ultrasonically treated at 18-25°C for 3-4 hours, 3-aminopropyltriethoxysilane is added, ultrasonically treated for 15-20 minutes, and then stirred for 10-12 hours, filtered, washed, and dried to obtain amination of molybdenum disulfide.

[0012] Further, the preparation of composite zirconium oxide includes the following steps: (1) zirconium nitrate, cerium nitrate aqueous solution and yttrium nitrate aqueous solution are mixed, citric acid and ethylene glycol are added, and the mixture is placed in an electric heating mantle and stirred. Nitric acid and ammonia water are added in sequence, and the mixture is kept at 78-82°C for 25-30 minutes. The temperature of the electric heating mantle is adjusted to 130°C, and the mixture is stirred until the solution burns to obtain a precursor, and then the mixture is kept at 795-805°C for 2-3 hours to obtain yttrium-cerium doped zirconium oxide; (2) Mix cerium nitrate, cobalt nitrate hexahydrate and methanol, add a mixture of 2-aminoterephthalic acid and methanol, and place in a water bath at 33-37°C for 5-6 hours. Add yttrium-cerium doped zirconium oxide, continue to keep warm for 16-18 hours, centrifuge, wash and dry to obtain composite zirconium oxide.

[0013] Further, the preparation of epoxy silicone resin comprises the following steps: 1) Phenyltriethoxysilane, methyltriethoxysilane, octamethylcyclotetrasiloxane, tetramethylcyclotetrasiloxane and toluene are mixed, a solid acid catalyst is added, the temperature is raised to 65-76°C and the temperature is kept for 2-3 hours, hexamethyldisiloxane and tetramethyldisiloxane are added, the temperature is kept for 2-3 hours, the mixture is filtered, the mixture is allowed to stand for stratification, and the mixture is distilled under reduced pressure to obtain a phenyl hydrogenated silicone resin; 2) Under nitrogen protection, phenyl hydrogenated silicone resin, 1-octadecene, allyl glycidyl ether and isopropanol are mixed, the temperature is raised to keep warm for 3-5 hours, and the epoxy silicone resin is obtained by vacuum distillation.

[0014] Compared with the prior art, the present invention has the following beneficial effects: The present invention provides a high-hardness precision injection mold and a preparation process thereof. By optimizing the process and components, a precision injection mold with high hardness, good wear resistance, high temperature resistance and a super-hydrophobic surface is prepared, thereby extending the service life of the precision injection mold and being beneficial to improving the apparent quality and mechanical properties of the injection molded product.

[0015] In order to improve the precision and apparent quality of the product and keep the plastic melt at a stable temperature and good fluidity in the mold during injection molding, the present invention adopts a laser cladding method to prepare a low thermal conductivity cladding layer on the inner surface of the mold, and uses Ni15 and composite zirconia as a cladding composite material. In order to improve the bonding strength between the cladding layer and the mold base steel, Ni15 is used as a powder and pre-clad on the surface of the mold base steel, thereby alleviating the problem of mismatching the thermal expansion coefficients of the cladding layer and the mold base steel. Ni15 and composite zirconia are selected as the cladding composite material, wherein Ni15 has the effect of improving the wettability of the composite material, and the introduction of composite zirconia gives the cladding layer low thermal conductivity and high corrosion resistance, thereby improving the precision and service life of the precision injection mold.

[0016] The composite zirconia is prepared by a combustion synthesis method using citric acid as a fuel and ethylene glycol as an additive to prepare yttrium-cerium co-doped zirconia. The introduction of rare earth elements is used to achieve the effect of refining the grains of the cladding layer and improving the surface quality of the cladding layer. In order to improve the uniformity of the dispersion of yttrium-cerium co-doped zirconia in the cladding layer, the yttrium-cerium co-doped zirconia is modified. A cerium and cobalt co-doped organic skeleton with 2-aminoterephthalic acid as a ligand is grown on the yttrium-cerium co-doped zirconia by a hydrothermal method. At the same time, the introduction of the cerium and cobalt co-doped organic skeleton is conducive to the laser modification treatment, thereby improving the various properties of the injection mold.

[0017] In order to improve the anti-stickiness and wear resistance of injection molds and based on the purpose of green development, epoxy silicone resin, composite zirconium oxide and amino molybdenum disulfide are used as fluorine-free protective coatings. In order to improve the uniformity of dispersion of molybdenum disulfide in the coating, lithium ion intercalation method is used to strip molybdenum disulfide, and 3-aminopropyltriethoxysilane is inserted into the sulfur atom missing sites generated during stripping by ultrasonic method to obtain amino molybdenum disulfide nanosheets, which improve the water resistance and wear resistance of the coating.

[0018] In the present invention, the epoxy silicone resin is used as a fluorine-free binder. In order to improve its heat resistance, phenyl triethoxysilane, methyl triethoxysilane, octamethylcyclotetrasiloxane, tetramethylcyclotetrasiloxane, hexamethyldisiloxane and tetramethyldisiloxane are first used as raw materials to prepare phenyl hydrogenated silicone resin; then, a phenyl silicone resin co-modified with a long-chain alkyl group and an epoxy group is synthesized as the epoxy silicone resin by a hydrosilylation reaction of the phenyl hydrogenated silicone resin with allyl glycidyl ether and 1-octadecene; and the epoxy group in the epoxy silicone resin is controlled to open the ring with the amino group in the aminated molybdenum disulfide and the composite zirconium oxide to construct a high-hardness, super-hydrophobic, highly wear-resistant and corrosion-resistant protective coating, thereby greatly improving the service durability of the injection mold. DETAILED DESCRIPTION

[0019] The following will be combined with the embodiments of the present invention to clearly and completely describe the technical solutions in the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0020] It should be noted that if the embodiments of the present invention involve directional indications such as up, down, left, right, front, and back, the directional indication is only used to explain a specific posture such as the relative position relationship between the components, the movement status, etc. If the specific posture changes, the directional indication will also change accordingly. In addition, the technical solutions between the various embodiments can be combined with each other, but it must be based on the ability of ordinary technicians in this field to implement. When the combination of technical solutions is contradictory or cannot be implemented, it should be considered that such a combination of technical solutions does not exist and is not within the protection scope required by the present invention.

[0021] The technical solution of the present invention is further described in detail below in conjunction with specific embodiments. It should be understood that the following embodiments are only used to explain the present invention, and are not used to limit the present invention.

[0022] Embodiment 1: A method for preparing a high-hardness precision injection mold, comprising the following steps: S1: grinding, washing and drying the mold in sequence to obtain a clean mold; S2: Using Ni15 as powder, laser cladding treatment is first performed on the surface of a clean mold to form a cladding base layer to obtain a pre-treated mold; The working conditions of laser cladding treatment are: spot diameter 3mm, power 1.8KW, scanning speed 700mm / min, multi-pass overlap rate 40%; S3: Ni15 and composite zirconia are mixed as a cladding composite material, and laser cladding treatment is performed on the surface of the pretreated mold to form a cladding layer to obtain a cladding mold; The mass ratio of Ni15 and composite zirconia is 2:1; S4: Mixing composite zirconium oxide, amino molybdenum disulfide, epoxy silicone resin and solvent to obtain a protective coating; The protective coating is composed of, by weight, 1 part of composite zirconium oxide, 1 part of amino molybdenum disulfide, 12 parts of epoxy silicone resin, and 52 parts of solvent; The mass ratio of the sum of the mass of the composite zirconium oxide and the amino molybdenum disulfide to the mass of the epoxy silicone resin is 1:6; The preparation of amination molybdenum disulfide comprises the following steps: 0.5 g of molybdenum disulfide powder and 18 mL of 0.5 M n-butyl lithium hexane solution were mixed, transferred to an autoclave, kept warm at 88° C. for 4 h, filtered, washed, and dried to obtain pretreated molybdenum disulfide; 0.25 g of pretreated molybdenum disulfide and 500 mL of deionized water were mixed, ultrasonically treated at 18° C. for 4 h, 0.5 g of 3-aminopropyltriethoxysilane was added, ultrasonically treated for 15 min, and then stirred for 10 h, filtered, washed, and dried to obtain amination of molybdenum disulfide; The preparation of the composite zirconium oxide comprises the following steps: (1) 1.7 g zirconium nitrate, 0.13 mL 0.4 mol / L cerium nitrate aqueous solution, 0.15 mL 1 mol / L yttrium nitrate aqueous solution were mixed, 7 mmol citric acid and 8.4 mmol ethylene glycol were added, the mixture was placed in an electric heating mantle and stirred, 24 µL nitric acid and 24 µL ammonia were added, the mixture was kept warm at 78 °C for 30 min, the temperature of the electric heating mantle was adjusted to 130 °C, the mixture was stirred until the solution burned to obtain a precursor, and then the mixture was kept warm at 795 °C for 3 h to obtain yttrium-cerium doped zirconium oxide; (2) 1 mmol of cerium nitrate, 1 mmol of cobalt nitrate hexahydrate, and 30 mL of methanol were mixed, and a mixed solution of 2 mmol of 2-aminoterephthalic acid and 30 mL of methanol was added, and the mixture was incubated in a water bath at 33° C. for 24 h, centrifuged, washed, and dried to obtain composite zirconium oxide; The preparation of the epoxy silicone resin comprises the following steps: 1) 5 g of phenyltriethoxysilane, 3 g of methyltriethoxysilane, 3.2 g of octamethylcyclotetrasiloxane, 2.4 g of tetramethylcyclotetrasiloxane, and 100 mL of toluene were mixed, 0.4 g of solid acid catalyst was added, the temperature was raised to 65°C and kept warm for 3 h, 1.6 g of hexamethyldisiloxane and 1.2 g of tetramethyldisiloxane were added, the temperature was kept warm for 2 h, filtered, allowed to stand and stratified, and vacuum distilled to obtain phenyl hydrogenated silicone resin; 2) Under nitrogen protection, 12 g of phenyl hydrogenated silicone resin, 1 g of 1-octadecene, 4 g of allyl glycidyl ether, and 2.7 g of isopropanol were mixed, the temperature was raised to keep warm for 3 hours, and the epoxy silicone resin was obtained by vacuum distillation; S5: spraying the protective coating on the surface of the mold after cladding, solidifying it to form a protective layer, and obtaining a high-hardness precision injection mold; the working conditions of the spraying treatment are: spraying pressure 0.5MPa, spraying rate 7m / min.

[0023] Embodiment 2: A method for preparing a high-hardness precision injection mold, comprising the following steps: S1: grinding, washing and drying the mold in sequence to obtain a clean mold; S2: Using Ni15 as powder, laser cladding treatment is first performed on the surface of a clean mold to form a cladding base layer to obtain a pre-treated mold; The working conditions of laser cladding treatment are: spot diameter 3mm, power 1.8KW, scanning speed 700mm / min, multi-pass overlap rate 40%; S3: Ni15 and composite zirconia are mixed as a cladding composite material, and laser cladding treatment is performed on the surface of the pretreated mold to form a cladding layer to obtain a cladding mold; The mass ratio of Ni15 and composite zirconia is 2:1; S4: Mixing composite zirconium oxide, amino molybdenum disulfide, epoxy silicone resin and solvent to obtain a protective coating; The protective coating is composed of 2 parts of composite zirconium oxide, 1.5 parts of amino molybdenum disulfide, 21 parts of epoxy silicone resin, and 67 parts of solvent in parts by mass; The mass ratio of the sum of the mass of the composite zirconium oxide and the amino molybdenum disulfide to the mass of the epoxy silicone resin is 1:6; The preparation of amination molybdenum disulfide comprises the following steps: 0.5 g of molybdenum disulfide powder and 18 mL of 0.5 M n-butyl lithium hexane solution were mixed, transferred to an autoclave, kept warm at 90° C. for 3.5 h, filtered, washed, and dried to obtain pretreated molybdenum disulfide; 0.25 g of pretreated molybdenum disulfide and 500 mL of deionized water were mixed, ultrasonically treated at 20° C. for 3.5 h, 0.5 g of 3-aminopropyltriethoxysilane was added, ultrasonically treated for 18 min, and then stirred for 11 h, filtered, washed, and dried to obtain amination of molybdenum disulfide; The preparation of the composite zirconium oxide comprises the following steps: (1) 1.7 g zirconium nitrate, 0.13 mL 0.4 mol / L cerium nitrate aqueous solution, and 0.15 mL 1 mol / L yttrium nitrate aqueous solution were mixed, 7 mmol citric acid and 8.4 mmol ethylene glycol were added, and the mixture was placed in an electric heating mantle and stirred. 24 µL nitric acid and 24 µL ammonia were added, and the mixture was kept at 80 °C for 26 min. The temperature of the electric heating mantle was adjusted to 130 °C, and the mixture was stirred until the solution burned to obtain a precursor, and then the mixture was kept at 800 °C for 2.5 h to obtain yttrium-cerium doped zirconium oxide. (2) 1 mmol of cerium nitrate, 1 mmol of cobalt nitrate hexahydrate, and 30 mL of methanol were mixed, and a mixed solution of 2 mmol of 2-aminoterephthalic acid and 30 mL of methanol was added, and the mixture was incubated in a water bath at 35° C. for 23 h, centrifuged, washed, and dried to obtain composite zirconium oxide; The preparation of the epoxy silicone resin comprises the following steps: 1) 5 g of phenyltriethoxysilane, 3 g of methyltriethoxysilane, 3.2 g of octamethylcyclotetrasiloxane, 2.4 g of tetramethylcyclotetrasiloxane, and 100 mL of toluene were mixed, 0.4 g of solid acid catalyst was added, the temperature was raised to 70°C and kept warm for 2.5 h, 1.6 g of hexamethyldisiloxane and 1.2 g of tetramethyldisiloxane were added, the temperature was kept warm for 2.5 h, filtered, allowed to stand and stratified, and vacuum distilled to obtain phenyl hydrogenated silicone resin; 2) Under nitrogen protection, 12 g of phenyl hydrogenated silicone resin, 1 g of 1-octadecene, 4 g of allyl glycidyl ether, and 2.7 g of isopropanol were mixed, the temperature was raised to keep warm for 4 hours, and the epoxy silicone resin was obtained by vacuum distillation; S5: spraying the protective coating on the surface of the mold after cladding, solidifying it to form a protective layer, and obtaining a high-hardness precision injection mold; the working conditions of the spraying treatment are: spraying pressure 0.6MPa, spraying rate 8m / min.

[0024] Embodiment 3: A method for preparing a high-hardness precision injection mold, comprising the following steps: S1: grinding, washing and drying the mold in sequence to obtain a clean mold; S2: Using Ni15 as powder, laser cladding treatment is first performed on the surface of a clean mold to form a cladding base layer to obtain a pre-treated mold; The working conditions of laser cladding treatment are: spot diameter 3mm, power 1.8KW, scanning speed 700mm / min, multi-pass overlap rate 40%; S3: Ni15 and composite zirconia are mixed as a cladding composite material, and laser cladding treatment is performed on the surface of the pretreated mold to form a cladding layer to obtain a cladding mold; The mass ratio of Ni15 and composite zirconia is 2:1; S4: Mixing composite zirconium oxide, amino molybdenum disulfide, epoxy silicone resin and solvent to obtain a protective coating; The protective coating is composed of 3 parts of composite zirconium oxide, 2 parts of amino molybdenum disulfide, 30 parts of epoxy silicone resin, and 83 parts of solvent in parts by mass; The mass ratio of the sum of the mass of the composite zirconium oxide and the amino molybdenum disulfide to the mass of the epoxy silicone resin is 1:6; The preparation of amination molybdenum disulfide comprises the following steps: 0.5 g of molybdenum disulfide powder and 18 mL of 0.5 M n-butyl lithium hexane solution were mixed, transferred to an autoclave, kept warm at 92° C. for 3 h, filtered, washed, and dried to obtain pretreated molybdenum disulfide; 0.25 g of pretreated molybdenum disulfide and 500 mL of deionized water were mixed, ultrasonically treated at 25° C. for 3 h, 0.5 g of 3-aminopropyltriethoxysilane was added, ultrasonically treated for 20 min, and then stirred for 12 h, filtered, washed, and dried to obtain amination of molybdenum disulfide; The preparation of the composite zirconium oxide comprises the following steps: (1) 1.7 g zirconium nitrate, 0.13 mL 0.4 mol / L cerium nitrate aqueous solution, 0.15 mL 1 mol / L yttrium nitrate aqueous solution were mixed, 7 mmol citric acid and 8.4 mmol ethylene glycol were added, the mixture was placed in an electric heating mantle and stirred, 24 µL nitric acid and 24 µL ammonia were added, the mixture was kept warm at 82 °C for 25 min, the temperature of the electric heating mantle was adjusted to 130 °C, the mixture was stirred until the solution burned to obtain a precursor, and then the mixture was kept warm at 805 °C for 2 h to obtain yttrium-cerium doped zirconium oxide; (2) 1 mmol of cerium nitrate, 1 mmol of cobalt nitrate hexahydrate, and 30 mL of methanol were mixed, and a mixed solution of 2 mmol of 2-aminoterephthalic acid and 30 mL of methanol was added, and the mixture was incubated in a water bath at 37° C. for 22 h, centrifuged, washed, and dried to obtain composite zirconium oxide; The preparation of the epoxy silicone resin comprises the following steps: 1) 5 g of phenyltriethoxysilane, 3 g of methyltriethoxysilane, 3.2 g of octamethylcyclotetrasiloxane, 2.4 g of tetramethylcyclotetrasiloxane, and 100 mL of toluene were mixed, 0.4 g of solid acid catalyst was added, the temperature was raised to 76 ° C and kept warm for 2 h, 1.6 g of hexamethyldisiloxane and 1.2 g of tetramethyldisiloxane were added, and the temperature was kept warm for 3 h, filtered, allowed to stand and stratified, and vacuum distilled to obtain phenyl hydrogenated silicone resin; 2) Under nitrogen protection, 12 g of phenyl hydrogenated silicone resin, 1 g of 1-octadecene, 4 g of allyl glycidyl ether, and 2.7 g of isopropanol were mixed, the temperature was raised to keep warm for 5 hours, and the epoxy silicone resin was obtained by vacuum distillation; S5: spraying the protective coating on the surface of the mold after cladding, solidifying it to form a protective layer, and obtaining a high-hardness precision injection mold; the working conditions of the spraying treatment are: spraying pressure 0.7MPa, spraying rate 9m / min.

[0025] Comparative Example 1: Taking Example 3 as the control group, zirconium oxide (Z431828: Aladdin reagent) was used to replace the composite zirconium oxide, and the other processes were normal.

[0026] Comparative Example 2: Example 3 was used as a control group, and amination of molybdenum disulfide was not prepared, and other processes were normal.

[0027] Comparative Example 3: Taking Example 3 as the control group, the epoxy silicone resin was replaced by silicone resin (99%, Nanjing Bermuda Biotechnology Co., Ltd.), and the other processes were normal.

[0028] In the embodiment and the comparative example, the thickness of the cladding base layer is 40 μm, the thickness of the cladding layer is 80 μm, and the thickness of the protective layer is 10 μm.

[0029] Sources of raw materials used (for demonstration purposes only): Mold (Q345 steel): by mass fraction, the chemical composition is 0.16% carbon, 0.42% silicon, 1.32% manganese, 0.25% chromium, 0.02% phosphorus, 0.25% nickel, 0.24% copper, and the balance is iron: solid acid catalyst YKCH8501: Tianjin Yunkai Resin Technology Co., Ltd.; Ni15: by mass fraction, the chemical composition is: 0.1% carbon, 22.4% silicon, 1.2% boron, 1.3% iron, and the balance is nickel; n-butyl lithium hexane solution (22%): Zhende Chemical Technology (Shanghai) Co., Ltd.; molybdenum disulfide powder M104968, 3-aminopropyltriethoxysilane A107147, zirconium nitrate Z190748, cerium nitrate C1 05378, yttrium nitrate Y106052, citric acid C108869, ethylene glycol E103319, cobalt nitrate hexahydrate C112729, 2-aminoterephthalic acid A151463, phenyltriethoxysilane T118551, methyltriethoxysilane T103634, octamethylcyclotetrasiloxane O160041, tetramethylcyclotetrasiloxane W132887, hexamethyldisiloxane H105443, tetramethyldisiloxane T110097, 1-octadecene O109487, allyl glycidyl ether A106314: Aladdin reagent; solvent (ethanol), nitric acid, ammonia water, methanol, toluene, isopropanol, analytical grade: Sinopharm reagent.

[0030] Performance test: The injection molds prepared in the embodiments and comparative examples were tested: Microhardness: measured by hardness tester, load selected 200g, interval 20μm, loading time 15s; hydrophobicity: characterized by water contact angle, tested with 2μL deionized water droplet; wear resistance: kept at 300℃ for 4h, taken out and cooled, rubbed 1cm back and forth 50 times with 800-grit sandpaper, and measured the water contact angle again. The change rate of water contact angle is qualified if it is 0-1% (including 1%), otherwise it is unqualified. The results are shown in Table 1; Table 1

[0031] The present invention provides a high-hardness precision injection mold and a preparation process thereof. By optimizing the process and components, a precision injection mold with high hardness, good wear resistance, high temperature resistance and a super-hydrophobic surface is prepared, thereby extending the service life of the precision injection mold and being beneficial to improving the apparent quality and mechanical properties of the injection molded product.

[0032] By comparing Example 3 with Comparative Example 1, it can be seen that in order to improve the precision and apparent quality of the product and keep the plastic melt at a stable temperature and good fluidity in the mold during injection molding, the present invention adopts a laser cladding method to prepare a low thermal conductivity cladding layer on the inner surface of the mold, and uses Ni15 and composite zirconia as a cladding composite material. In order to improve the bonding strength between the cladding layer and the mold base steel, Ni15 is used as a powder and pre-clad on the surface of the mold base steel, thereby alleviating the problem of mismatching the thermal expansion coefficients of the cladding layer and the mold base steel. Ni15 and composite zirconia are selected as a cladding composite material, wherein Ni15 has the effect of improving the wettability of the composite material, and the introduction of composite zirconia gives the cladding layer low thermal conductivity and high corrosion resistance, thereby improving the precision and service life of the precision injection mold.

[0033] The composite zirconia is prepared by a combustion synthesis method using citric acid as a fuel and ethylene glycol as an additive to prepare yttrium-cerium co-doped zirconia. The introduction of rare earth elements is used to achieve the effect of refining the grains of the cladding layer and improving the surface quality of the cladding layer. In order to improve the uniformity of the dispersion of yttrium-cerium co-doped zirconia in the cladding layer, the yttrium-cerium co-doped zirconia is modified. A cerium and cobalt co-doped organic skeleton with 2-aminoterephthalic acid as a ligand is grown on the yttrium-cerium co-doped zirconia by a hydrothermal method. At the same time, the introduction of the cerium and cobalt co-doped organic skeleton is beneficial to the modification of the laser, thereby improving the various properties of the injection mold.

[0034] By comparing Example 3 with Comparative Example 2, it can be seen that in order to improve the anti-stickiness and wear resistance of the injection mold and for the purpose of green development, epoxy silicone resin, composite zirconium oxide, and amino molybdenum disulfide are used as fluorine-free protective coatings. In order to improve the uniformity of the dispersion of molybdenum disulfide in the coating, lithium ion intercalation method is used to strip molybdenum disulfide, and 3-aminopropyltriethoxysilane is inserted into the sulfur atom missing site generated during stripping by ultrasonic method to obtain amino molybdenum disulfide nanosheets, thereby improving the water resistance and wear resistance of the coating.

[0035] By comparing Example 3 with Comparative Example 3, it can be seen that in the present invention, the epoxy silicone resin is used as a fluorine-free binder. In order to improve its heat resistance, phenyl triethoxysilane, methyl triethoxysilane, octamethylcyclotetrasiloxane, tetramethylcyclotetrasiloxane, hexamethyldisiloxane and tetramethyldisiloxane are first used as raw materials to prepare phenyl hydrogenated silicone resin; then, a phenyl silicone resin co-modified with a long-chain alkyl group and an epoxy group is synthesized as the epoxy silicone resin by the hydrosilylation reaction of the phenyl hydrogenated silicone resin with allyl glycidyl ether and 1-octadecene, and the epoxy group in the epoxy silicone resin is controlled to open the ring with the amino group in the aminated molybdenum disulfide and the composite zirconium oxide to construct a high hardness, super hydrophobic, highly wear-resistant and corrosion-resistant protective coating, thereby greatly improving the durability of the injection mold.

[0036] The above descriptions are only embodiments of the present invention and are not intended to limit the patent scope of the present invention. All equivalent structural changes made using the present invention specification under the inventive concept of the present invention, or direct / indirect applications in other related technical fields, are included in the patent protection scope of the present invention.

Claims

1. A method for preparing a high-hardness precision injection mold, characterized in that: The following steps are involved: S1: grinding, washing and drying the mold in sequence to obtain a clean mold; S2: Using Ni15 as powder, laser cladding treatment is first performed on the surface of a clean mold to form a cladding base layer to obtain a pre-treated mold; S3: Ni15 and composite zirconia are mixed as a cladding composite material, and laser cladding treatment is performed on the surface of the pretreated mold to form a cladding layer to obtain a cladding mold; S4: Mixing composite zirconium oxide, amino molybdenum disulfide, epoxy silicone resin and solvent to obtain a protective coating; S5: spraying the protective coating on the surface of the mold after cladding, curing, forming a protective layer, and obtaining a high-hardness precision injection mold.

2. The method for preparing a high-hardness precision injection mold according to claim 1, characterized in that: The working conditions of laser cladding treatment are: spot diameter 3mm, power 1.8KW, scanning speed 700mm / min, and multi-pass overlap rate 40%.

3. The method for preparing a high-hardness precision injection mold according to claim 1, characterized in that: In the cladding composite material, the mass ratio of Ni15 to composite zirconia is 2:

1.

4. The method for preparing a high-hardness precision injection mold according to claim 1, characterized in that: The working conditions of the spraying treatment are: spraying pressure 0.5-0.7MPa, spraying rate 7-9m / min.

5. The method for preparing a high-hardness precision injection mold according to claim 1, characterized in that: The protective coating comprises, by weight, 1-3 parts of composite zirconium oxide, 1-2 parts of amino molybdenum disulfide, 12-30 parts of epoxy silicone resin, and 52-83 parts of solvent.

6. The method for preparing a high-hardness precision injection mold according to claim 1, characterized in that: The mass ratio of the sum of the mass of the composite zirconium oxide and the amino molybdenum disulfide to the epoxy silicone resin is 1:

6.

7. The method for preparing a high-hardness precision injection mold according to claim 1, characterized in that: The preparation of amination molybdenum disulfide comprises the following steps: Molybdenum disulfide powder and n-butyl lithium hexane solution are mixed, transferred to an autoclave, kept warm at 88-92°C for 3-4 hours, filtered, washed, and dried to obtain pretreated molybdenum disulfide; the pretreated molybdenum disulfide and deionized water are mixed, ultrasonically treated at 18-25°C for 3-4 hours, 3-aminopropyltriethoxysilane is added, ultrasonically treated for 15-20 minutes, and then stirred for 10-12 hours, filtered, washed, and dried to obtain amination of molybdenum disulfide.

8. The method for preparing a high-hardness precision injection mold according to claim 1, characterized in that: The preparation of the composite zirconium oxide comprises the following steps: (1) zirconium nitrate, cerium nitrate aqueous solution and yttrium nitrate aqueous solution are mixed, citric acid and ethylene glycol are added, and the mixture is placed in an electric heating mantle and stirred. Nitric acid and ammonia water are added in sequence, and the mixture is kept at 78-82°C for 25-30 minutes. The temperature of the electric heating mantle is adjusted to 130°C, and the mixture is stirred until the solution burns to obtain a precursor, and then the mixture is kept at 795-805°C for 2-3 hours to obtain yttrium-cerium doped zirconium oxide; (2) Mix cerium nitrate, cobalt nitrate hexahydrate and methanol, add a mixture of 2-aminoterephthalic acid and methanol, and place in a water bath at 33-37°C for 5-6 hours. Add yttrium-cerium doped zirconium oxide, continue to keep warm for 16-18 hours, centrifuge, wash and dry to obtain composite zirconium oxide.

9. The method for preparing a high-hardness precision injection mold according to claim 1, characterized in that: The preparation of the epoxy silicone resin comprises the following steps: 1) Phenyltriethoxysilane, methyltriethoxysilane, octamethylcyclotetrasiloxane, tetramethylcyclotetrasiloxane and toluene are mixed, a solid acid catalyst is added, the temperature is raised to 65-76°C and the temperature is kept for 2-3 hours, hexamethyldisiloxane and tetramethyldisiloxane are added, the temperature is kept for 2-3 hours, the mixture is filtered, the mixture is allowed to stand for stratification, and the mixture is distilled under reduced pressure to obtain a phenyl hydrogenated silicone resin; 2) Under nitrogen protection, phenyl hydrogenated silicone resin, 1-octadecene, allyl glycidyl ether and isopropanol are mixed, the temperature is raised to keep warm for 3-5 hours, and the epoxy silicone resin is obtained by vacuum distillation.

10. A high hardness precision injection mold, characterized in that: Prepared according to the preparation method according to any one of claims 1 to 9.